Design and performance of mass-produced sideband separating SIS mixers for ALMA band 4 receivers. (30th July 2015) - Kojima, Takafumi; Kuroiwa, Koichi; Takahashi, Toshikazu; Fujii, Yumi; Uzawa, Yoshinori; Asayama, Shin'ichiro; Noguchi, Takashi
Abstract: We have designed and mass-produced low-noise sideband separating superconductor–insulator–superconductor (SIS) mixers for the Atacama Large Millimeter/submillimeter Array (ALMA) band 4 over the frequency range of 125–163 GHz. An integrated design was adopted for the band 4 sideband separating (2SB) mixer block because of the advantages it offers in terms of compactness, reduced testing time and lower cost. The mixer chip was designed to be robust for handling errors to avoid performance degradation caused by generation of the higher order mode in the mixer chip slot. Detailed analyses revealed its robustness and ability to ensure mass production of the 2SB mixers. Using the robust mixer design in addition to well-established waveguide technologies, all of the 2SB mixers met ALMA specifications for noise temperature and image rejection ratio.